2015
DOI: 10.4143/crt.2015.060
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Statistics in Korea: Incidence, Mortality, Survival, and Prevalence in 2012

Abstract: PurposeThe aim of this study was to report nationwide cancer statistics in Korea, including incidence, mortality, survival, and prevalence, and their trends.Materials and MethodsIncidence data from 1993 to 2012 were obtained from the Korea National Cancer Incidence Database, and vital status was followed through December 31, 2013. Mortality data from 1983 to 2012 were obtained from Statistics Korea. Crude and age-standardized rates for incidence, mortality, and prevalence, and relative survival were calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
461
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(467 citation statements)
references
References 10 publications
4
461
0
2
Order By: Relevance
“…and colon/rectum cancers were the main causes of cancer death. Heart disease, diabetes mellitus and hypertensive diseases associated with MetS were also leading causes of death in Korea, accounting for approximately 16 % of all deaths (20) . Prevalence of MetS in Korea was 24·9 % in 1998 and increased to 31·3 % in 2007 (Fig.…”
Section: Change Of the Status Of Metabolic Syndrome And Cancermentioning
confidence: 99%
“…and colon/rectum cancers were the main causes of cancer death. Heart disease, diabetes mellitus and hypertensive diseases associated with MetS were also leading causes of death in Korea, accounting for approximately 16 % of all deaths (20) . Prevalence of MetS in Korea was 24·9 % in 1998 and increased to 31·3 % in 2007 (Fig.…”
Section: Change Of the Status Of Metabolic Syndrome And Cancermentioning
confidence: 99%
“…Colorectal cancer is generally less common in Asia than in the Western world (Ferlay et al, 2013;Liu et al, 2015) but is becoming of greater importance and is generally on the increase, for example in Korea (Jung et al, 2015), Turkey (Seydaoğlu et al, 2013) and in Iran, for example in Kermanshah and Hamadan provinces; however, change did not reach significance in Ilam and Kurdistan provinces (Abdifard et al, 2013), increasing East Azerbaijan (Somi et al, 2014) and Kerman (Roya and Abbas, 2013). In China, age-specific rates of colorectal remained relatively stable in one study (Zhou et al, 2015) and in Japan, colorectum and lung (males), showed a pattern of increasing incidence and mortality rates until the mid-1990s, stabilizing or decreasing thereafter (Katanoda et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In a study conducted in Japan, synchronous esophageal cancer and GC were detected in 23 patients (8.0%) and 8 patients (2.8%) of 287 patients with HNSCC during initial endoscopic examination. 8 Histologically, most GCs are adenocarcinoma, and the risk factors for GC are Helicobacter pylori infection and certain life habits, such as salty diet, smoking, and alcohol consumption.…”
mentioning
confidence: 99%